Life Course Effects of Adverse Childhood Experiences on Health-Related Quality of Life - Son, Chong-Hwan (Archives of Business Research, 2019)
This study examines the duration of the effects of adverse childhood experiences (ACEs) on health-related quality of life (HRQOL) throughout the lifespan with the adult population by five age groups. The study conducts a cross-sectional regression analysis using the 2012 Behavioral Risk Factor Surveillance System (BRFSS) data. In the empirical results, the estimated coefficients of all ACE scores for the mentally unhealthy days exceed the coefficients for the physically unhealthy days in all age groups. It suggests that the adverse effects of ACEs on mental health outcomes are more significant than the effects of ACEs on physical health outcomes. In conclusion, the empirical results indicate that the adverse impacts of cumulative ACE scores on both physical and mental health outcomes are onset at the early stage of adulthood and persist into the late stage of life. Noticeably, the adverse effects slightly drop and rebound at the middle age group, ages 40-49, and then the adverse associations of ACEs on HRQOL remain throughout the life course.